Cataloging practices of four theological and seminary school libraries a survey - Manglal-lan, Christine M. (1997)
This research focuses on the cataloging practices of four theological and seminary school libraries belonging to the Asia Graduate School of Theology (AGST), with the purpose of determining the strengths and weaknesses in the cataloging and classification activities of the four libraries under study. The study seeks to: 1) identify the people doing the cataloging work; 2) determine their qualifications and whether they are engaged in tasks other than cataloging; 3) identify the practices and policies involved in the cataloging and classification of library materials; and 4) find out if computers are used in cataloging. The descriptive research method used: questionnaires and informal interviews.